PERAN GURU DALAM MENUMBUHKAN KEMAMPUAN KOGNITIF MELALUI MODEL PEMBELAJARAN BEYOND CENTER AND CIRCLE TIME (BCCT) PADA SENTRA BALOK DI RA RAUDLATUL ULUM GANJARAN-MALANG - Rohma, Mustafiatur; Hikmah, Fitrotul (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2023)
The role of teachers in development related to intellectual, social-emotional, moral and motoric development. The aim of this research is to describe cognitive abilities through the learning model (BCCT) for group A at RA Raudlatul Ulum Ganjaran-Gondanglegi. This research uses descriptive-qualitative research methods and Library Research research type with data collection techniques, namely observation, interviews and documentation. The results of the research and discussion show that cognitive development through the BCCT model includes problem solving/reasoning, concept formation, imitation/memory, and association/clarification. Techniques for designing play platforms include arranging facilities and infrastructure according to the shape of the room, grouping tables and chairs according to needs, classroom walls can be used to attach facilities that are used as learning resources and the results of children's activities, placing and storing play equipment arranged in such a way according to their function, Play equipment for safety activities is arranged in the room. Research suggestions for teachers can collaborate learning models with various learning centers for early childhood.